GAMBARAN PENGETAHUAN DAN SIKAP IBU MENYUSUI TERHADAP TEKNIK MENYUSUI YANG BENAR DI WILAYAH KERJA PUSKESMAS AIR DINGIN TAHUN 2023 - Laura Zeffira; Maryeti Marwazi; Hondrizal, Hondrizal; Irdawaty Izrul; Dwita Widya Kartika (Yayasan Nusantara Hasana Berdikari, 2023)
Exclusive breast milk (ASI) is breastfeeding as early as possible after delivery which is given without a schedule and is not given any other additional food or drinks until the age of 6 months. The success of exclusive breastfeeding is influenced by many factors, both internal and external. . Internal factors include mother's age, nutritional status, and education level, while external factors are knowledge about exclusive breastfeeding, health workers and the mass media. To find out the description of the knowledge and attitudes of breastfeeding mothers towards correct breastfeeding techniques in the Working Area of the Air Cold Health Center. The scope of this research is breastfeeding mothers who have children aged 0-24 months. The research was conducted in December- January 2022. The type of research is descriptive. The study population was breastfeeding mothers who had children aged 0-24 months with a total of 200 samples using the consecutive sampling technique. Univariate data analysis was presented in the form of a frequency distribution and bivariate analysis using the Kruskall-Wallis test, data processing using the computerized SPSS program IBM version 25.0. Research shows that mother's knowledge is 73% high and mother's attitude is 86.5%. These results indicate that the majority of breastfeeding mothers in the Air Cold Health Center Work Area have high knowledge and a positive attitude.